Dexmedetomidine, agitated delirium, and “off-label” drugs - Carrasco, Genís; Baeza, Nacho; Cabré, Lluís (Journal of Thoracic Disease, 2016)
We appreciate the comments by Parker et al. (1) and Knauert et al. (2) concerning our recent manuscript entitled “Dexmedetomidine for the treatment of hyperactive delirium refractory to haloperidol in non-intubated ICU patients: A non-randomized controlled trial” (3). We are agreed with the most of reviewer’s considerations. However, we would like to add three reflections that may be interesting for the readers. The first relates to the current position of this alpha-2 agonist on the healthcare market. A second comment intends to respond to some interesting assertions from the reviewers that, in our opinion, could be controversial. The third and final comment is addressed to reflect on the future of the research on intensive care unit (ICU) delirium.